PERAN GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS IV - Selvina Salsabila; Aris Gumilar; Dayu Retno Puspita (STKIP Subang, 2023)
This study is entitled The Role of Teachers in Improving the Motivation of Grade IV Students at SDN Sudimara 6 Ciledug Tangerang City. The purpose of this study was to determine the Role of Teachers in Improving the Motivation of Grade IV Students at SDN Sudimara 6 Ciledug Tangerang City. This research uses descriptive and qualitative research. The subjects in this study were grade IV homeroom teachers. This research was conducted at SDN Sudimara 6 in 2023. The data collection techniques used in this research are observation, interview, and documentation techniques. Data analysis techniques used in this research are data reduction techniques, data presentation, and conclusion drawing. The results of the research that has been done show that the role of the teacher as a demonstrator is that the homeroom teacher IV teaches the material in accordance with the ATP and syllabus. The role of the teacher as a classroom manager is to ensure that the homeroom teacher IV knows the situation and is able to handle students while in class. The role of the teacher as a mediator or facilitator is that the homeroom teacher IV adjusts the media from the lesson plan. The role of the teacher as evaluator is to ensure that the homeroom teacher has provided authentic assessment and collected data from the results of summative evaluation, formative evaluation, and daily assessment. The role of the teacher as a motivator is that the homeroom teacher IV provides learning encouragement to students by telling inspirational stories.